Problems Of Metabolic Syndrome and Its Components in The Modern World - Gulchexra Khamroevna Razhabova; Nigora Gafurovna Ashurova (Genius Journals, 2021)
MS is a special problem as it is a combination of various risk factors and multiplies the likelihood of adverse outcomes; Isolation of MS aims to substantiate the need to start drug therapy even before the appearance of a specific pathology - hypertension, ischemic heart disease and diabetes mellitus-2; The concept of "metabolic syndrome" as a synonym for "risk factors" most fully meets the requirements of practical medicine.
Keywords: metabolic risk factors; components of MS; Arterial hypertension